2015
DOI: 10.1177/0146167215571089
|View full text |Cite
|
Sign up to set email alerts
|

When the Model Fits the Frame

Abstract: In health-promotional campaigns, positive and negative role models can be deployed to illustrate the benefits or costs of certain behaviors. The main purpose of this article is to investigate why, how, and when exposure to role models strengthens the persuasiveness of a message, according to regulatory fit theory. We argue that exposure to a positive versus a negative model activates individuals' goals toward promotion rather than prevention. By means of two experiments, we demonstrate that high levels of pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…In addition, most previous research has focused on how regulatory fit improves attitudes (e.g. Bosone, Martinez, & Kalampalikis, 2015; Cesario et al, 2013). Our research demonstrated that when individuals have initially negative attitudes toward an option, regulatory non-fit can be a more effective way to improve their attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most previous research has focused on how regulatory fit improves attitudes (e.g. Bosone, Martinez, & Kalampalikis, 2015; Cesario et al, 2013). Our research demonstrated that when individuals have initially negative attitudes toward an option, regulatory non-fit can be a more effective way to improve their attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas previous studies measured attitude after manipulating regulatory non-fit (Koenig et al, 2009; Vaughn, Malik, et al, 2006; Vaughn, O’Rourke, et al, 2006), we examined attitude change , focusing on how the effects of regulatory non-fit on attitude change may differ as a function of initial attitude. In addition, most previous research has focused on how regulatory fit improves attitudes (e.g., Bosone, Martinez, & Kalampalikis, 2015; Cesario et al, 2013). Our research demonstrated that when individuals have initially negative attitudes toward an option, regulatory non-fit can be a more effective way to improve their attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…By forming vivid mental simulations of events, narrative information can enable the formation of an alignment with the protagonist persuading greater levels of acceptance of the message’s intended response ( Green and Clark, 2013 ), and thus mediating the effectiveness of message adoption and behavioural change ( Lee et al, 2011 ). We argue that the effectiveness of presenting the risks of air pollution in a narrative format will partly depend on the influence such a format has on individuals’ efficacy appraisal, including self-efficacy and response-efficacy ( Bosone et al, 2015 ). Self-efficacy refers to a person’s belief about their ability to engage in a behaviour and is often associated with response efficacy, which is the perceived effectiveness of one’s behavioural change ( Witte and Allen, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…RFT has been applied to further investigate which form of message framing enhances the persuasiveness of advertisements targeting viewers with distinct psychological traits. Previous studies have combined RFT with message framing [ 16 , 35 , 36 ]. Rothman and Slovey [ 37 ] indicated that message framing can be manipulated with RFT by using two methods.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a gain-framed message could be aired during a show that primes a promotion orientation and a loss-framed message could be aired during a show that primes a prevention orientation. The aforementioned studies show that persuasiveness can be enhanced when the presented message fits the regulatory focus of the intended audience [ 36 ]. Therefore, this study proposed the following hypotheses and research framework ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%